PENINGKATAN UMKM KECAMATAN CIPAYUNG MELALUI STRATEGI PEMASARAN DIGITAL - Nurzaman, Fahrul; Asril Basry; I Gede Agus Suwartane; Dian Gustina; Nafisah Yuliani; Susi Wagiyati P; Dwi Dinariana (Universitas Mataram, 2024)
The development of technology and communication is increasingly sophisticated, the choice of using marketing through Social Media is the main choice made by business people, now the use of Social Media has become the main pillar in delivering information. One of the advantages of Social Media is that it has a lot of potential for the advancement of a business. So interested are Indonesians in Social Media services that various platforms continue to arrive in Indonesia. Various new Social Media platforms continue to be introduced, and interestingly always find the right market share in Indonesia. Micro, Small and Medium Enterprises (MSMEs) utilize internet media as a means of online marketing to obtain a satisfactory market share. Currently, the internet is very accessible to anyone around the world, including MSME business people who use the internet as a means of providing and sharing information about products offered to consumers online. The purpose of this PKM activity is that MSME players, especially in the Cipayung sub-district area, East Jakarta, can utilize Social Media and internet technology to advance their business in the following ways: a) providing counseling in utilizing various Social Media platforms to support businesses, b) providing motivation and knowledge of entrepreneurship and entrepreneurship, c) explaining internet technology and information technology to provide opportunities in business development.